Analisis Peraturan Guru Dalam Meningkatkan Disiplin Siswa - Diniyah, Wikayatul; Rohmah, Ni’matur; Kholiq, Abdul (STAI Publisistik Thawalib Jakarta, 2024)
The aim of this research is to explain teacher regulations in enhancing student discipline at SDN Tlonto Raja VIII. The study was conducted qualitatively using a case study approach. Data collection methods included interviews, observations, and documentation. The results indicate that teacher mastery of regulations is crucial for improving student discipline. Teachers need to understand and implement school, national, and classroom management regulations to create an organized learning environment and foster positive student behavior. Teacher role modeling affects student behavior both in and outside of school. Cooperation among the principal, teachers, and other educational staff is essential for consistent discipline implementation. Regulations include general rules (such as punctuality, uniforms, and prohibition of banned items) and specific rules related to classroom management. The categorization of rules and the application of varying sanctions (light, moderate, severe) support orderliness and effective discipline.